Multiple submandibular duct (Wharton’s duct) calculi of unusual size and shape - Krishnappa, B. D. (Springer-Verlag, 2010)
Salivary gland stones are most common in the ductal system of submandibular glands and are calcified. A rare case of multiple submandibular duct (Wharton’s duct) calculi of unusual size and shape in a 42-year-old male patient, who presented with pain and swelling in the region of submandibular gland and hence reported. Sometimes a small stone comes out into the mouth on its own or with gentle probing. However in this case a small intra-oral procedure was needed to remove the stones.